Pathogenicity of Clinical OXA-48 Isolates and Impact of the OXA-48 IncL Plasmid on Virulence and Bacterial Fitness - Hamprecht, Axel; Sommer, Julian; Willmann, Matthias; Brender, Christina; Stelzer, Yvonne; Krause, Felix F.; Tsvetkov, Tsvetan; Wild, Florian; Riedel-Christ, Sara; Kutschenreuter, Julia; Imirzalioglu, Can; Gonzaga, Aitor; et al. (Frontiers in Microbiology, 2019)
OXA-48 is the most common carbapenemase in Enterobacterales in Germany and one of the most frequent carbapenemases worldwide. Several reports have associated blaOXA–48 with a virulent host phenotype. To challenge this hypothesis, 35 OXA-48-producing clinical isolates of Escherichia coli (n = 15) and Klebsiella pneumoniae (n = 20) were studied in vitro, in vivo employing the Galleria mellonella infection model and by whole-genome sequencing. Clinical isolates belonged to 7 different sequence types (STs) in E. coli and 12 different STs in K. pneumoniae. In 26/35 isolates blaOXA–48 was located on a 63 kb IncL plasmid. Horizontal gene transfer (HGT) to E. coli J53 was high in isolates with the 63 kb IncL plasmid (transconjugation frequency: ∼103/donor) but low in isolates with non-IncL plasmids (<10–6/donor). Several clinical isolates were both highly cytotoxic against human cells and virulent in vivo. However, 63 kb IncL transconjugants generated from these highly virulent isolates were not more cytotoxic or virulent when compared to the recipient strain. Additionally, no genes associated with virulence were detected by in silico analysis of OXA-48 plasmids. The 63 kb plasmid was highly stable and did not impair growth or fitness in E. coli J53. In conclusion, OXA-48 clinical isolates in Germany are diverse but typically harbor the same 63 kb IncL plasmid which has been reported worldwide. We demonstrate that this 63 kb IncL plasmid has a low fitness burden, high plasmid stability and can be transferred by highly efficient HGT which is likely the cause of the rapid dissemination of OXA-48 rather than the expansion of a single clone or gain of virulence.